First Biomimetic Fixation for Resurfacing Arthroplasty: Investigation in Swine of a Prototype Partial Knee Endoprosthesis. (1st July 2019) - Rogala, Piotr; Uklejewski, Ryszard; Winiecki, Mariusz; Dąbrowski, Mikołaj; Gołańczyk, Jacek; Patalas, Adam
Abstract : Resurfacing hip and knee endoprostheses are generally embedded in shallow, prepared areas in the bone and secured with cement. Massive cement penetration into periarticular bone, although it provides sufficient primary fixation, leads to the progressive weakening of peri-implant bone and results in failures. The aim of this paper was to investigate in an animal model the first biomimetic fixation of components of resurfacing arthroplasty endoprostheses by means of the innovative multispiked connecting scaffold (MSC-Scaffold). The partial resurfacing knee arthroplasty (RKA) endoprosthesis working prototype with the MSC-Scaffold was designed for biomimetic fixation investigations using reverse engineering methods and manufactured by selective laser melting. After Ca-P surface modification of bone contacting surfaces of the MSC-Scaffold, the working prototypes were implanted in 10 swines. Radiological, histopathological, and micro-CT examinations were performed on retrieved bone-implant specimens. Clinical examination confirmed very good stability (4 in 5-point Likert scale) of the operated knee joints. Radiological examinations showed good implant fixation (radiolucency less than 2 mm) without any signs of migration. Spaces between the MSC-Scaffold spikes were penetrated by bone tissue. The histological sections showed newly formed trabecular bone tissue between the spikes, and the trabeculae of periscaffold bone were seen in contact with the spikes. The micro-CT results showed the highest percentage of bone tissue ingrowths into the MSC-Scaffold at a distance of 2.5÷3.0 mm from the spikes bases. The first biomimetic fixation for resurfacing arthroplasty was successfully verified in 10 swines investigations using RKA endoprosthesis working prototypes. The performed research shows that the MSC-Scaffold allows for cementless and biomimetic fixation of resurfacing endoprosthesis components in periarticular cancellous bone.